Mengangkat Nilai Singkong Lokal: Analisis Business Model Canvas pada Produk Mocaf KWT Ngudi Rejeki - Wibowo, Astrid Wahyu Adventri (Jurnal Ilmu Administrasi dan Bisnis, 2025)
The Ngudi Rejeki Women Farmers Group (KWT) in Gunungkidul Regency has developed a mocaf (Modified Cassava Flour) production business as a solution to increase the added value of local cassava, which has a low selling price. However, limitations in production capacity and business strategy hinder the potential development of the business. This study aims to analyze the business model of KWT Ngudi Rejeki using the Business Model Canvas (BMC) framework that includes nine main elements of the business, and provide strategic recommendations based on the analysis results. The research approach is descriptive qualitative with a case study method, where data is collected through in-depth interviews, direct observation, and document review. The results of the analysis show that although KWT has a good business foundation, there are several areas that require improvement, such as product diversification, adoption of modern technology, expansion of distribution channels, and development of strategic partnerships. The contribution of this research lies in the formulation of a more innovative and measurable business strategy, which is expected to strengthen the competitiveness and business sustainability of KWT Ngudi Rejeki in national and international markets. In addition, this research provides policy recommendations in the form of government support and related institutions in terms of technology training, business assistance, and promotion of local products.